Measuring the Effectiveness of Social Media at Online Discussion Forum Modifikasi.com - Angriawan, Rendra Deny; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2013)
The rapid growth of business process is affected by technology development at the time. Social media, which is a relatively new form of information technology development, have a potential to bring a revolution or huge changes at this time and for the future, a development which have to be noticed by the business owners so they can keep growing in this rapidly changing of business situation like today. Forums or discussion boards are the longest established form of online social media. They most commonly exist around specific topics and interest, for example cars or music. Discussion board or forum is one of the most favorable social media form by the internet users because it is the most used by some communities to gather and share in a certain interest or hobby. Modifikasi.com, or to be shortened as ModCom, is one of the biggest online discussion forum in Indonesia. It has a certain theme, which is an automotive world, and has a huge number of members. The purpose of doing this research is to analyzing effectiveness of the use of social media in online discussion forum Modifikasi.com by using the measurement of social media ROI, analyzing the position of the company at this time by using the Strategic Options for Social Media Measurement approach method, evaluating the effectiveness and the position of online discussion forum Modifikasi.com and creating marketing strategies. The research was conducted through desk research, interviews, and surveys. Respondents in this study are member of Modifikasi.com forum. Given this research, it is known the effectiveness of social media on Modifikasi.com in terms of brand awareness, brand engagement, and word of mouth, by comparing with competitorsâ€™ efforts in social media, to determine the appropriate measures for the increase of the effectiveness and ROI of Modifikasi.com in the future. The purpose of the social media effort is to increase brand awareness, brand engagement, as well as word of mouth from brand Modifikasi.comÂ Keywords: Social Media, Forum Discussion, Social Media ROI, Social Media Measurement, Strategic Options, Brand Awareness, Brand Engagement, Word Of Mouth.